Case Study of Recognition Patterns in Haunted People Syndrome - Houran, James; Laythe, Brian (Frontiers in Psychology, 2022)
Haunted People Syndrome (HP-S) denotes individuals who recurrently report various ‘supernatural’ encounters in everyday settings ostensibly due to heightened somatic-sensory sensitivities to dis-ease states (e.g., marked but sub-clinical levels of distress), which are contextualized by paranormal beliefs and reinforced by perceptual contagion effects. This view helps to explain why these anomalous experiences often appear to be idioms of stress or trauma. We tested the validity and practical utility of the HP-S concept in an empirical study of an active and reportedly intense ghostly episode that was a clinical referral. The case centered on the life story of the primary percipient, a retired female healthcare worker. Secondary percipients included her husband and adult daughter, all of whom reported an array of benign and threatening anomalies (psychological and physical in nature) across five successive residences. Guided by prior research, we administered the family online measures of transliminality, sensory-processing sensitivity, paranormal belief, locus of control, desirability for control, and a standardized checklist of haunt-type phenomena. The primary percipient also completed a measure of adverse childhood events and supplied an event diary of her anomalous experiences. We found reasonably consistent support for HP-S from a set of quantitative observations that compared five proposed syndrome features against the family members’ psychometric profiles and the structure and contents of their anomalous experiences. Specifically, the S/O anomalies both correlated with the family’s scores on transliminality and paranormal belief, as well as elicited attributions and reaction patterns aligned with threat (agency) detection. There was some evidence of perceptual congruency among the family members’ anomalous experiences as well. Putative psi cannot be ruled out, but we conclude that the family’s ordeal fundamentally involved the symptoms and manifestations of thin (or ‘permeable’) mental boundary functioning in the face of unfavorable circumstances or overstimulating environments and subsequently acerbated by poor emotion regulation, histrionic and catastrophizing reactions, and active confirmation biases.